p53 and apoptosis - Oren, Moshe (Henry Stewart Talks, 2007)
p53 as a tumor suppressor, Regulation of transcription by p53, Activation of p53 by oncogenic stress, Transcriptional and non-transcriptional mechanisms for p53- mediated apoptosis, Regulation of p53 by Mdm2, Evolutionary conservation of p53 function, Mutant p53 gain of function, p53-based cancer therapy